2022
DOI: 10.3390/nu14204393
|View full text |Cite
|
Sign up to set email alerts
|

Would You Buy Plant-Based Beef Patties? A Survey on Product Attribute Preference and Willingness to Pay among Consumers in Liaoning Province, China

Abstract: Carbon emissions from the production of beef account for the majority of carbon emissions from animal husbandry, and animal husbandry, in turn, is the main driver of global carbon emissions. At present, there are relatively few studies of consumer preferences for beef substitutes, especially in developing countries. However, plant-based meat is of great significance in solving the tense relationship between supply and demand, ensuring sustainable development, further improving food safety, and improving animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…However, this interest is not reflected in the analysis of the hedonic price from which it emerges as only one Apulian producer (i.e., Cerealitalia) has presented on the label the indication of the geographical origin of the legumes used. Despite this lack of interest from companies, the literature appears to be in agreement with our result, showing how this attribute is already relevant for different types of products: plant-based beef meatballs [49], wine [21], sea urchins [52], oil [53] and legumes [54]. Depending on the social and cultural changes that have taken place, the needs and preferences expressed by consumers have changed, passing from the satisfaction of subjective needs and those related to the health of the individual, to ethical and environmental needs, paying attention to the community.…”
Section: Interpretation and Comparison Of The Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, this interest is not reflected in the analysis of the hedonic price from which it emerges as only one Apulian producer (i.e., Cerealitalia) has presented on the label the indication of the geographical origin of the legumes used. Despite this lack of interest from companies, the literature appears to be in agreement with our result, showing how this attribute is already relevant for different types of products: plant-based beef meatballs [49], wine [21], sea urchins [52], oil [53] and legumes [54]. Depending on the social and cultural changes that have taken place, the needs and preferences expressed by consumers have changed, passing from the satisfaction of subjective needs and those related to the health of the individual, to ethical and environmental needs, paying attention to the community.…”
Section: Interpretation and Comparison Of The Resultssupporting
confidence: 89%
“…So, this shows that consumers are more health conscious and choose protein-, fiber-and carbohydrate-enriched snacks over carbohydrate-enriched and protein-deficient snacks [47]. In the same way, our respondents are very attentive to the type of ingredients, nutritional indications and snack labeling, a constant that is also found in many other publications [48][49][50]. In fact, it is now established that consumers seek satisfaction in food, but at the same time they are increasingly aware of the fact that food contributes significantly to their health and well-being [51].…”
Section: Interpretation and Comparison Of The Resultssupporting
confidence: 72%
“…Our study found that respondents in both countries were willing to pay a premium for "traceable" labeling; this result aligns with the findings of several earlier studies (e.g., Ortega et al, 2011;Wu et al, 2015;Zhou et al, 2022). This indicates the positive attitude of young consumers in both countries toward the establishment of traceability systems for alternative meats.…”
Section: Traceabilitysupporting
confidence: 91%
“…The fourth attribute was the traceability of the burger patty. Traceability systems ensure food safety, and consumers are usually willing to pay a premium for "traceable" labeling (Ortega et al, 2011;Zhou et al, 2022). The last attribute was carbon footprint.…”
Section: Unlabeled Dce Designmentioning
confidence: 99%
“…Customers can easily compare product information, payment methods, prices and discounts on their mobile phones 10 . Several studies have investigated customer choices on digital platforms through price comparison (see References 11 and 12). Customer online reviews also reflect the impact of price comparisons on customer choices (see Reference 13).…”
Section: Literature Reviewmentioning
confidence: 99%